2020
DOI: 10.1007/978-3-030-65414-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Box Merging Strategies and Uncertainty Estimation Methods in Multimodel Object Detection

Abstract: This paper examines the impact of different box merging strategies for sampling-based uncertainty estimation methods in object detection. Also, a comparison between the almost exclusively used softmax confidence scores and the predicted variances on the quality of the final predictions estimates is presented. The results suggest that estimated variances are a stronger predictor for the detection quality. However, variance-based merging strategies do not improve significantly over the confidence-based alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To merge predictions, we used the mean method. Roza et al [30] implemented several different box merging strategies, and showed significant variations on sample-based uncertainty estimates resulting from different strategies. Based on their results, we used the mean method, which had the best performance overall.…”
Section: Output Clustering and Mergingmentioning
confidence: 99%
“…To merge predictions, we used the mean method. Roza et al [30] implemented several different box merging strategies, and showed significant variations on sample-based uncertainty estimates resulting from different strategies. Based on their results, we used the mean method, which had the best performance overall.…”
Section: Output Clustering and Mergingmentioning
confidence: 99%